The effect of sodium hypochlorite enamel pretreatment on the shear bond strength of fissure sealant using a resin-modified glass ionomer cement and a fluoride-releasing self-etch resin adhesive - Najmeh Mohammadi; Ali Karimkhani; Rafat Bagheri; David J Manton (Wolters Kluwer Medknow Publications, 2021)
Background: The relative high caries risk of pits and fissures highlights the importance of protecting these areas. The aim is to determine the effect of sodium hypochlorite (NaOCl) on the shear bond strength (SBS) of resin-based pit and fissure sealant (RBPFS) material to enamel using resin-modified glass ionomer cement (RMGIC) and fluoride-releasing self-etch resin (FRSE) adhesives. Materials and Methods: In this in vitro study extracted third molar teeth without carious lesions or defects were divided into five experimental groups (n = 20). Group A: (Control group) etch (35% phosphoric acid) for 15 s and RBPFS applied. Group B: Etch for 15 s, FRSE and RBPFS applied. Group C: Pretreated with 5% NaOCl and similar steps to Group B. Group D: Etch for 15 s then RMGIC bonding agent and RBPFS applied. Group E: Pretreated with 5% NaOCl and then similar steps to Group D. SBS was determined using a universal testing machine. The tested specimens were examined under a field-emission scanning electron microscope. Data were analyzed using one-way ANOVA and post hoc Tukey's tests (P=0.05). Results: A statistically significant difference between the test groups was observed; Group C showed the highest SBS mean value (7.52 ± 2.74 MPa) and Group D showed the lowest (4.48 ± 1.81 MPa) (P < 0.001). Pretreatment with NaOCl increased the SBS of fissure sealant when Riva bond LC was used (P = 0.049). Conclusion: The use of NaOCl as pretreatment can increase the SBS of RBPFS to enamel using RMGIC adhesive. FRSE adhesive did not show improvement in SBS values using pretreatment.